Race and the Sanctioning of Misdemeanor Defendants - Moricette, Patrick (American journal of criminal justice, 2023)
The dearth of research on the relationship between a defendant's race and the severity of sanction in misdemeanor cases is concerning, given that these cases comprise the majority of criminal cases in the U.S. The extant literature on the subject is mixed. Some studies find a noteworthy relationship between race and severity of punishment, while others report that the association is weak or in the opposite direction of what would be expected based on racial bias. It is important to study this issue further, as the consequences of a misdemeanor arrest and conviction can be significant and can have adverse consequences for an individual in society. This study contributes to the literature by creating an ordinal scale ranging from low to high severity to measure the different types of punishments typically imposed on misdemeanor defendants. The data on misdemeanor defendants were obtained from the case management system of the prosecutor's office from three counties in a large Florida jurisdiction. Results show that the odds of receiving a less severe sanction are 24.5% higher for Black than White misdemeanor defendants. However, while Black defendants are sanctioned more leniently overall, they are less likely than Whites defendants to be convicted and more likely to receive a no-sanction outcome for their misdemeanor crimes.